Apical Positioned Flap with a Combination of Mucograft and Fibro-Gide for Augmenting Keratinized Gingiva with Thin Gingival Phenotype: A Case Report - Zhu, Xin-Rui; Liu, Yi (European Journal of Dentistry, 2025)
The width and thickness of keratinized gingiva play a crucial role in the periodontal health and long-term stability of natural teeth. Noncrosslinked xenogeneic collagen matrix (Mucograft) has demonstrated favorable outcomes in augmenting keratinized gingival width (KGW), though its effect on increasing gingival thickness remains suboptimal. In contrast, crosslinked xenogeneic collagen matrix (Fibro-Gide) effectively enhances keratinized gingival thickness (KGT) but is unable to increase KGW. The aim of this study is to investigate the combined transplantation of Mucograft and Fibro-Gide in patients with thin gingival biotypes and insufficient KGW, evaluating whether this approach can simultaneously achieve both widening and thickening of the keratinized gingiva. This study selected a patient with a thin gingival biotype and insufficient KGW. A horizontal incision was made 0.5 mm above the mucogingival junction, and a partial-thickness flap was elevated and repositioned apically. Fibro-Gide was placed at the apical aspect of the surgical site, enveloped by the partial-thickness flap, while its coronal aspect was positioned in close contact with Mucograft, which was exposed in the surgical area. Both graft materials were securely sutured to the periosteum, ensuring partial contact with the keratinized gingiva. At the 12-month follow-up, the KGW increased from 1.5 to 3.5 mm and the KGT increased from 0.8 to 2.1 mm. For patients with a thin gingival biotype, the combined transplantation of Mucograft and Fibro-Gide can simultaneously augment the width of keratinized gingiva and increase gingival thickness.This technique has the following advantages:
Keywords: Mucograft; Fibro-Gide; keratinized gingiva; thin gingival phenotype; apical positioned flap